2010
DOI: 10.1111/j.1462-5822.2009.01425.x
|View full text |Cite
|
Sign up to set email alerts
|

The chemokine-binding protein encoded by the poxvirus orf virus inhibits recruitment of dendritic cells to sites of skin inflammation and migration to peripheral lymph nodes

Abstract: SummaryOrf virus (ORFV) is a zoonotic parapoxvirus that induces acute pustular skin lesions in sheep and humans. ORFV can reinfect its host and the discovery of several secreted immune modulatory factors that include a chemokine-binding protein (CBP) may explain this phenomenon. Dendritic cells (DC) are professional antigen presenting cells that induce adaptive immunity and their recruitment to sites of infection in skin and migration to peripheral lymph nodes is critically dependent on inflammatory and consti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 39 publications
1
49
0
Order By: Relevance
“…The chemokine-binding spectrum and affinities of the BPSV CBP were consistent with those reported for the CBP from its fellow parapoxvirus, orf virus. [13][14][15]18 After establishing the ability of the CBP to inhibit a broad spectrum of chemokines, we investigated its efficacy in vivo. We found that intravenous administration of the CBP after transient cerebral ischemia largely prevented stroke-induced increases in circulating levels of key chemokines in association with milder neurological deficit at 24 hours.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The chemokine-binding spectrum and affinities of the BPSV CBP were consistent with those reported for the CBP from its fellow parapoxvirus, orf virus. [13][14][15]18 After establishing the ability of the CBP to inhibit a broad spectrum of chemokines, we investigated its efficacy in vivo. We found that intravenous administration of the CBP after transient cerebral ischemia largely prevented stroke-induced increases in circulating levels of key chemokines in association with milder neurological deficit at 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…11 Many viruses secrete proteins that bind chemokines as a means of evading the host immune system and ensuring their own survival. 12 Recently, a novel type of chemokine-binding protein (CBP) has been identified from orf virus, [13][14][15] and fellow parapoxviruses, bovine papular stomatitis virus (BPSV), and pseudocowpox virus. 16,17 This CBP shows high-affinity binding for both human and mouse CC, CXC, and C chemokines and has been demonstrated to prevent inflammatory monocyte recruitment to the skin and to block dendritic cell trafficking to peripheral lymph nodes.…”
Section: February 2015mentioning
confidence: 99%
See 2 more Smart Citations
“…Myxoma viruses deficient in M-T1(vCCI) have a subtle phenotype, with an increase in leukocyte infiltration but no significant difference in disease progression or mortality (18,25). In addition, mouse studies of ORF virus infection, a zoonotic parapoxvirus, shown to encode vCCI-like chemokine binding protein (26), demonstrated that ORF virus (ORFV) vCCI blocks the recruitment of immature and mature dendritic cells to the skin and lymph nodes and inhibits T cell responsiveness in lymph nodes (26,27). The role of herpesvirusencoded chemokine binding proteins in pathogenesis and immune modulation remains poorly understood, in part due to lack of the appropriate experimental host.…”
mentioning
confidence: 99%